Gait models and mechanical energy in three cross-country skiing techniques - Pellegrini, B.; Zoppirolli, C.; Bortolan, L.; Zamparo, P.; Schena, F. (The Journal of Experimental Biology, 2014)
Walking on snow is tough, so for centuries people have attached planks to their feet to improve movement across winter landscapes. More recently, cross-country skiing has become a popular sport, with sophisticated equipment that is painstakingly prepared before major competitions. Biomechanists Barbara Pellegrini and Chiara Zoppirolli from the University of Verona, Italy, work with top international athletes to assess and improve their performance. So, when cross-country skiers began coming to their lab at the Centre for Research in Mountain Sport and Health to optimise their performance, their colleague Federico Schena realised that they needed to learn more about the basic biomechanics of the different cross-country ski techniques. Having already shown why double poling (where only the arms are used for propulsion) is the most efficient method on flat surfaces, while diagonal stride (where skiers use both their arms and legs, pushing off at the same time with the alternate arm and leg) is most effective up hill and double poling with kick (where the skiers push off intermittently with one leg while double poling) is used to transition between the two techniques, Pellegrini, Paola Zamparo and colleagues have now turned their attention to how the different techniques relate to more conventional forms of motion, such as walking and running (p. 3910).